COPOLYMERIZATION OF VINYL CHLORIDE WITH - Matyakubova D.Sh; Matyakubova N.Sh; Xidirova M.N (Journal of Science in Medicine and Life, 2023)
In this study, the kinetics of copolymerization of VK with 2- phenylacryloylaminobenzimidazole (FAB) is investigated. The content of FAB in the copolymers was determined by elemental analysis and also confirmed by UV spectra of solutions of copolymer samples in tetrahydrofuran. The kinetics of copolymerization of VC with FAB was studied by the gravimetric method.